13 The association between the dose of glucocorticoids and health-related quality of life in patients with systemic lupus erythematosus: a cross-sectional study. (April 2019) - Miyawaki, Yoshia; Shimizu, Sayaka; Ogawa, Yusuke; Sada, Ken-ei; Ichinose, Kunihiro; Yoshimi, Ryusuke; Ohno, Shigeru; Yajima, Nobuyuki; Fukuhara, Shunichi
Abstract : Background: Glucocorticoids (GC) is a mainstay of treatment for systemic lupus erythematosus (SLE) but generally known to affect the health-related quality of life (HRQOL). The aim in this study is to investigate the association between the current dose of GC and HRQOL in SLE patients. Methods: This was a cross-sectional study using baseline data of nationwide SLE patients registry (LUNA) from April 2018 through September 2018. Participants were outpatients with SLE aged 20 years or older. The exposure was the current dose of GC (an equivalent of daily prednisolone). The primary outcome was the HRQOL score of Lupus Patient Reported Outcome (LupusPRO). We included age, sex, and damage in covariates to be particularly considered for the effect of GC-related damage. Damage was divided into GC-related damage and other damage using the SLICC damage index (SDI). GC-related damage was defined as the presence of diabetes mellitus, osteonecrosis, osteoporotic fractures and cataracts. We used a linear regression model to assess the association between the current dose of GC and the HRQOL and further evaluated which of the current daily dose of GC and the GC-related damage has a greater impact on HRQOL from standardized -coefficients. Multiple imputation was performed for missing data. Results: Of the 188 enrolled patients, 84% were female and the median age was 44 (interquartile range [IQR] 35–55) years. The median SLEDAI was 4 (IQR 2–8) and the median of daily prednisolone dosage was 5 (IQR 4–9) mg. The median HRQOL score was 70 (IQR 53–84). HRQOL was significantly associated with the daily dose of prednisolone (=−0.50 [95% confidence interval (CI) −0.99 to −0.02]), SDI 1 (=−8.2 [95%CI −14.0 to −2.4]) and female (=−11.8 [95%CI −19.8 to −3.9]). Multiple linear regression analysis showed that the daily prednisolone dose was significantly associated with HRQOL (=−0.88 [95%CI −1.45 to −0.31]). The current daily dose of GC had a greater influence on HRQOL than the GC-related damage (standardized=−0.23 vs standardized=−0.20). After multiple imputation of missing values, our findings did not substantially change (=−0.66 [95%CI −1.14 to −0.17]). Conclusions: The daily dose of GC was associated with HRQOL among SLE patients rather than the GC-related damage. These findings may help to understand the effects of GC treatment on HRQOL. Funding Source(s): None